A wireless network detection and control system for intelligent agricultural greenhouses based on NB-IOT technology. Issue 1 (January 2021) - Ye, Haitao; Yang, Yongjie; Zhu, Linyu
Abstract: In order to reduce unnecessary labor input in agriculture and maximize production efficiency, a NB-IoT technology based wireless network detection system for intelligent agricultural greenhouse plants was designed. Through the emerging Internet of Things technology NB-IoT[1], the system can conduct remote real-time monitoring and intelligent control of the growing environment of crops in agricultural greenhouses[2]. In agricultural greenhouses layout based on stm32 microcontroller to shed internal environment parameters in a wireless sensor network for data acquisition, and then collected data through the I 2 C [3]protocol to micro controller, the controller will receive the data transmission to the NB - IoT module, uploaded to the cloud, finally received by remote terminal and displayed to the user. Similarly, users can also remotely issue control commands to the microcontroller in the greenhouse through the terminal interactive interface, so as to realize the unmanned intelligent control of the environment in the greenhouse.